What employers want : job prospects for less-educated workers - Holzer, Harry J., 1957- (Multi-City Study of Urban Inequality., 1996)
What Employers Want is the first book to replace conjecture about today's job market with first-hand information gleaned from employers about who gets hired. Drawn from a survey of over 3,000 employers in four major metropolitan areas - Atlanta, Boston, Detroit, and Los Angeles - this volume provides a wealth of data on what jobs are available to the less educated, in what industries, what skills they require, where they are located, what they pay, and how they are filled.